Synthesis of Thiol-Modified Hemicellulose, Its Biocompatibility, Studies, and Appraisal as a Sustained Release Carrier of Ticagrelor - Zaman, Muhammad; Bajwa, Rabia Imtiaz; Qureshi, Omer Salman; Rehman, Atta Ur; Saeed, Sadaf; Amjad, Muhammad Wahab; Ghafoor Raja, Maria Abdul; Hussain, Muhammad Ajaz (Frontiers in Pharmacology, 2021)
Background: Nature has always been considered as the primary source of pharmaceutical ingredients. A variety of hemicelluloses, as well as their modified forms, have been under investigation. Herein, a study was designed to explore the biocompatibility of hemicellulose and its modified form (thiolated hemicellulose) as well as its potential as a pharmaceutical excipient. Method: For thiol modification thiourea was used as the thiol donor, HCl as the catalytic reagent, and methanol was used for washing purposes. Modified polymers were characterized for physicochemical characteristics, including surface morphology, the amorphous or crystalline nature of the particles, modification of polymer by FTIR, and biocompatibilities. For acute oral toxicity study, a single dose of 2 g/kg was administered to albino rats of 200 g average weight (n = 3). Polymers were evaluated as pharmaceutical excipients by preparing compressed tablets of antiplatelet drug (Ticagrelor), followed by various quality control tests, such as swelling index, thickness and diameter, disintegration, and in-vitro drug release. Results: From the results, it was observed that thiol modification has been successfully accomplished as characteristic peaks belonging to –SH group appeared at 2667.7691 cm−1 in FTIR scan. The modified polymer was found safe in the use concentration range, confirming their safe use for in vivo analysis. No significant effect has been observed in the behavior, biological fluid (blood), or on vital organs. Thiolated hemicellulose was found to be an excellent drug retarding polymer as 8 h of dissolution studies showed that 67.08% of the drug has been released. Conclusion: Conclusively, incorporation of thiol moiety made the polymer more mucoadhesive with, and a worthy carrier of, the drug with good biocompatibilities.